Survey Of GNSS Coordinates Systems - Szabova, Martina; Duchon, Frantisek (European Scientific Journal, ESJ, 2016)
The use of satellite positioning systems to determine position in reference frame can introduce serious practical difficulties. The problem can be in the fields of navigation, map revision or cadastral surveying. It arises because in local area the local coordinate system were used. The problem can be solved by transformation between coordinates frame. Global navigation satellite systems (GNSS) don’t use same reference frame and it is important to know transformation between this systems. This paper works with information of many international organizations and their documents. It contains information about reference coordinate system of GNSS, information about local coordinates system used in North America, UK, and Europe.